Comparation Study of The Use Naftalena From Coal Tar Waste with Camper Naphtalene As Concrete Admixture - Sumarno Agung; Syafwandi Syafwandi; Adelia Rizky Fatmawati; Sumiyati Sumiyati (Yayasan Ahmar Cendekia Indonesia, 2020)
Concrete is a mixture of Portland cement or other hydraulic cement, fine aggregate, coarse aggregate, and water, with or without additives (admixture). The naphthalene superplasticizer used comes from the distillation of coal tar and a little from the rest of petroleum, but there is also camphor naphthalene. Where camphor grains contain 250-500 mg of naphthalene. Naphthalene is mostly produced from coal tar distillation, and a little from the rest of the fractionation of petroleum, by the molecular formula (C10H8) and in the form of two unified benzene rings. This compound is volatile, volatile even in the form of solids. The vapor produced is flammable. The purpose of this study was to determine the effect of the use of naphthalene from coal tar waste with camphor naphthalene as concrete admixture, and determine the effect of naphthalene from coal tar waste with camphor naphthalene on concrete toughness, density, water absorption, of concrete compressive strength. It is expected that the use of naphthalene can reduce the use of cement, and reduce water use. But it does not reduce the strength of the concrete so as to reduce costs in making concrete. The variations in the use of camphor naphthalene and coal tar naphthalene are 20%, 30%, 40%.